Transformation of Russian-Chinese Interaction in Central Asia : from Strategic Partnership to Asymmetric Rivalry - Г. Жаксыгулова (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì)
The article examines the transformation of Russian-Chinese interaction in Central Asia against the background of China's growing presence in the region, which is particularly relevant in the context of global geopolitical changes and increasing international tensions.